Strategic positioning of tourist destinations- analyzing the role of perceived meaningfulness. (December 2021) - Rejikumar, G.; Ajitha, Aswathy Asokan; Jose, Ajay; Mathew, Sonia
Abstract: This study analyzed the cognitive and affective components of destination image in the perception of foreign tourists visiting Indian destinations by exploring conceptual constructs, namely 'Post-visit Destination Image' and 'Perceived Meaningfulness.' The exploratory factor analysis of the responses of foreign tourists (n = 242) on items related to the major constructs significant in tourist behavior such as destination quality, perceived meaningfulness, and post-visit destination image confirmed the existence of multi-dimensional structure. Additionally, the empirical validation of the theoretical framework developed on the tenents of stimulus-organism-response paradigm with the constructs using structural equation modeling established significant relationships helpful to understand many new travel motivations. The study established that perceived meaningfulness has a significant mediating role in predicting tourist referral/revisit intentions from positive perceptions about destination quality and post-visit destination image. The observations from the study helped to identify six types of travel motivations useful in developing niche markets for positioning Indian destinations. The identified travel motivations, namely 'physical meaningfulness seeking, ' 'eternal meaningfulness seeking, ' social meaningfulness seeking, ' 'nature-loving, ' 'hospitality appreciating, ' and 'uniqueness exploring, ' offer directions to destination marketers to revamp destination attributes for destination marketing.